Endocannabinoids Produced by White Adipose Tissue Modulate Lipolysis in Lean but Not in Obese Rodent and Human - Buch, Chloé; Muller, Tania; Leemput, Julia; Passilly-Degrace, Patricia; Ortega-Deballon, Pablo; Pais de Barros, Jean-Paul; Vergès, Bruno; Jourdan, Tony; Demizieux, Laurent; Degrace, Pascal (Frontiers in Endocrinology, 2021)
White adipose tissue (WAT) possesses the endocannabinoid system (ECS) machinery and produces the two major endocannabinoids (ECs), arachidonoylethanolamide (AEA) and 2-arachidonoylglycerol (2-AG). Accumulating evidence indicates that WAT cannabinoid 1 receptors (CB1R) are involved in the regulation of fat storage, tissue remodeling and secretory functions but their role in controlling lipid mobilization is unclear. In the present study, we used different strategies to acutely increase ECS activity in WAT and tested the consequences on glycerol production as a marker of lipolysis. Treating lean mice or rat WAT explants with JLZ195, which inhibits ECs degrading enzymes, induced an increase in 2-AG tissue contents that was associated with a CB1R-dependent decreased in lipolysis. Direct treatment of rat WAT explants with AEA also inhibited glycerol production while mechanistic studies revealed it could result from the stimulation of Akt-signaling pathway. Interestingly, AEA treatment decreased lipolysis both in visceral and subcutaneous WAT collected on lean subjects suggesting that ECS also reduces fat store mobilization in Human. In obese mice, WAT content and secretion rate of ECs were higher than in control while glycerol production was reduced suggesting that over-produced ECs may inhibit lipolysis activating local CB1R. Strikingly, our data also reveal that acute CB1R blockade with Rimonabant did not modify lipolysis in vitro in obese mice and human explants nor in vivo in obese mice. Taken together, these data provide physiological evidence that activation of ECS in WAT, by limiting fat mobilization, may participate in the progressive tissue remodeling that could finally lead to organ dysfunction. The present findings also indicate that acute CB1R blockade is inefficient in regulating lipolysis in obese WAT and raise the possibility of an alteration of CB1R signaling in conditions of obesity.